“Acting out of Fear”: Queer Resistance During the Military Dictatorship in Brazil - Cintra Santos, Henrique (SQS – Suomen Queer-tutkimuksen Seuran lehti, 2023)
Amid the Brazilian military dictatorship, at a time when moral repression authorized police persecution, the queer community marched the streets demanding an end to such violence. On June 13th, 1980, one thousand people came out in downtown São Paulo for the first organized queer demonstration in Brazilian history. This demonstration intended to denounce the police violence perpetuated in the center of São Paulo by the so-called Operation Cleansing, which had as its main promoter the police’s precinct chief Richetti and queer bodies as one of its main targets. The event is analyzed with a focus on the study of emotions, mainly the concept of fear. Fear is conceptualized both as a tool of institutional control by the military regime and as a propeller of collective queer resistance against violence perpetuated by the State. Keywords: queer history, Brazilian history, emotion